Akulturasi Ajaran Siwa-Buddha Di Pura Pagulingan Desa Manukaya Gianyar - Cokorda Agung Semara Dalem Pemayun (Kamaya: Jurnal Ilmu Agama, 2019)
This research was conducted on the author's interest in the study of the theology of harmony in Bali. The harmony between religious communities in the middle of the island of Bali is not only influenced by a national consensus on political and social stability, but also because of local wisdom about acculturation in aspects of religion. The Shiva teachings which dominate and are recognized as a majority stream and even animate most Hindu values ​​in Bali do not forget to accommodate and harmonize themselves with other teachings, one of which is Buddhism. from that, the existence of Buddhism is still developing today. One of the reflections of the union of Shiva-Buddhist teachings can be found in Pagulingan Temple, Manukaya Village. This research is descriptive qualitative field research. The primary data sources in this study were Pagulingan Temple and Hindus and Buddhists as pengempon. Data collection is done using the snow ball technique. The results of this study are Acculturation of the Shiva-Buddha Teachings in Pura Pagulingan including (1) the history of the union of Shiva-Buddhas traced from India to the Archipelago, (2) the arrival of Shiva-Buddhism teachings in Manukaya Village, as the initial conditions for the development of Shiva-Teachings Buddha (3) The Process of Acculturation of the Shiva-Buddha Teachings which became the first focus, and (4) Pelinggih Pajenengan as a form of Acculturation. The driving factors for acculturation include (1) Cultural Value Factors, (2) Religious System Factors, (3) Social Factors. Implications of Acculturation in the Teachings of Shiva-Buddhists in Pagulingan Temple include (1) Social Implications and (2) Theological Implications.